Grundtvig and the Descent into Hell - Grundtvig, N. F. S. (Grundtvig-studier, 2016)
The following special section on Grundtvig’s poem I Kveld blev der banketpaa Helvedes Port [This Night came a Knocking on Hell’s Fortress-Gate]includes a new unrhymed metrical English translation of the poem withselect commentary by S.A.J. Bradley, followed by two articles, the firstby K.E. Bugge about the genesis of the poem and the Descent theme in Grundtvig’s thinking; and the second by S.A.J. Bradley concerning the Anglo-Saxon poems which Grundtvig indicates were his inspiration to I Kveld and a small cluster of other hymns which he wrote for the Danish Church.